1984
DOI: 10.1039/dt9840000621
|View full text |Cite
|
Sign up to set email alerts
|

Studies of phosphazenes. Part 17. Reaction of hexachlorocyclotriphosphazatriene with N-methylethanolamine: X-ray crystal structure of a dispirocyclotriphosphazatriene, N3P3(NMeCH2CH2O)2Cl2

Abstract: Abhängig vom stöchiometrischen Verhältnis der Reaktanden (I 23, I :6 bzw. I : I2), der Reaktionszeit und ‐temp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

1984
1984
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 2 publications
(2 reference statements)
2
14
0
2
Order By: Relevance
“…A and 4-B). These results showed that the substituent effects on bond parameters of P 3 N 3 ring were proportional to the number of substituents on the same phosphorus atom and it could be attributed to electron-releasing character of 1,4-benzodioxan-6-amino groups comparing to withdrawing chlorine substituent [43][44][45]. All of these observations were compatible with the previous studies in the literature [16,20,43,46].…”
Section: Crystal Structure Determinationsupporting
confidence: 93%
See 1 more Smart Citation
“…A and 4-B). These results showed that the substituent effects on bond parameters of P 3 N 3 ring were proportional to the number of substituents on the same phosphorus atom and it could be attributed to electron-releasing character of 1,4-benzodioxan-6-amino groups comparing to withdrawing chlorine substituent [43][44][45]. All of these observations were compatible with the previous studies in the literature [16,20,43,46].…”
Section: Crystal Structure Determinationsupporting
confidence: 93%
“…These results showed that the substituent effects on bond parameters of P 3 N 3 ring were proportional to the number of substituents on the same phosphorus atom and it could be attributed to electron-releasing character of 1,4-benzodioxan-6-amino groups comparing to withdrawing chlorine substituent [43][44][45]. All of these observations were compatible with the previous studies in the literature [16,20,43,46]. Compounds 7a (2-trans-4) and 7c (2-trans-6) were structural isomers in which the eight-membered cyclotetraphosphazene ring (P 4 N 4 ) was non-geminal bis-substituted with two 1,4-benzodioxan-6-amino-moieties on two sequential phosphorous atoms (P1 and P2) in compound 7a while on two diagonal phosphorous atoms (P1 and P3) in compound 7c (Figs.…”
Section: Crystal Structure Determinationmentioning
confidence: 83%
“…2,2-Spiro(N-methylethanolamino)-4,4,6, 6-tetrachlorocyclotriphosphazene, N 3 P 3 (MeNC 2 H 4 O)Cl 4 , was prepared applying the literature method [23]. The IR spectra were obtained using an FT BOMEM MB102 spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…Although the bond lengths and bond angles of the cyclotriphosphazene rings, (PN) 3 , of all compounds (2-6) are found within the normal range for many cyclotriphosphazenes [38][39][40], there are small differences in the P-N bond lengths and N-P-N bond angles because of the substitution by the 1,2-ethanedioxy moiety.…”
Section: Characterization Of the Compounds By X-ray Crystallographymentioning
confidence: 95%